Firehouse - Halberstam, David 1934-2007 (Hyperion, 2002)
This book is about Engine 40, Ladder 35, located on the West Side of Manhattan near Lincoln Center. On the morning of September 11, 2001, two rigs carrying thirteen men set out from this firehouse, only one would return. The reader watches the day unfold as the men are called to duty while their families wait for new of them. One comes to understand the culture of the firehouse itself. Why gifted men do this and why in so many instances they are eager to follow in their father's footsteps and serve in so dangerous a profession. And why it is not just a job, but a calling as well.